2015
DOI: 10.1002/jts.21992
|View full text |Cite
|
Sign up to set email alerts
|

Military Sexual Assault, Gender, and PTSD Treatment Outcomes of U.S. Veterans

Abstract: This study examined whether gender and military sexual assault (MSA) were associated with psychiatric severity differences at initiation of treatment for posttraumatic stress disorder (PTSD) and whether MSA and gender predicted psychiatric treatment outcomes. Male (n = 726) and female (n = 111) patients were recruited from 7 U.S. Department of Veterans Affairs (VA) PTSD specialty intensive treatment programs and completed an intake survey; 69% (n = 574) of the participants completed a 4-month postdischarge fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
2
45
1
Order By: Relevance
“…Lifetime experience of sexual assault is calculated among all males (n = 1268), since 2 of the 18 males who never had sex, reported having been the victims of sexual assault Nevertheless, our results show higher prevalence of sexual dysfunction among women than men, mirroring findings from the 2006 French sexual health survey [21]. The substantial gender gap across a range of sexual health concerns [14,27,28] has led to the development of women health service in the US military, among veterans [29] as well as in the US Navy, through the Sexual health and responsibility program (SHARP) [16]. French Armed forces have yet to develop such a programmatic approach.…”
Section: Discussionsupporting
confidence: 71%
“…Lifetime experience of sexual assault is calculated among all males (n = 1268), since 2 of the 18 males who never had sex, reported having been the victims of sexual assault Nevertheless, our results show higher prevalence of sexual dysfunction among women than men, mirroring findings from the 2006 French sexual health survey [21]. The substantial gender gap across a range of sexual health concerns [14,27,28] has led to the development of women health service in the US military, among veterans [29] as well as in the US Navy, through the Sexual health and responsibility program (SHARP) [16]. French Armed forces have yet to develop such a programmatic approach.…”
Section: Discussionsupporting
confidence: 71%
“…With women having an increasingly larger presence in the military, it is important to evaluate whether intensive PTSD treatment programs work equally well for men and women and for different trauma types (i.e., combat and military sexual trauma [MST]). One large Veteran’s Administration (VA) study combining data across seven different PTSD intensive treatment programs showed that sex and a history of military sexual assault did not predict treatment outcome [ 18 ]. However, this study was limited by the fact that they combined data across very different types of treatment programs and overall the treatment effect sizes were small, suggesting that these programs were not as effective as the intensive outpatient programs [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, female veterans and those with MST histories are more likely to receive pharmacological treatment for mental health conditions through primary care rather than the more effective evidence-based psychosocial treatments for PTSD [i.e., Prolonged Exposure (PE); Foa et al, 2007)], offered through VA specialty care clinics (Chatterjee et al, 2009; Maguen et al, 2010). This represents a missed opportunity since recent data indicate that PTSD treatment outcomes do not differ based on MST status (Tiet, Levya, Blau, Turchik, & Rosen, 2015). Thus, given adequate access to VA care, veterans with MST histories are likely to benefit from treatment.…”
Section: Introductionmentioning
confidence: 99%